Strategi manajemen pembelajaran berbasis AI untuk meningkatkan kemampuan literasi numerasi selaras dengan SDG 4 - Srie Faizah Lisnasari; Jainab Jainab; Datten Datten; Pelista Pelista; Mhd. Rafi’i Ma’arif Tarigan; Abu Nizar Bahri Ibrahim (Fakultas Tarbiyah dan Ilmu Keguruan UIN Profesor Kiai Haji Saifuddin Zuhri Purwokerto, 2025)
This study aims to explore and analyze the effectiveness of Artificial Intelligence (AI)-based learning management strategies in improving numeracy literacy skills of Elementary School Teacher Education (PGSD) students in the era of society 5.0. Using a mixed-method approach, data were collected through in-depth interviews, classroom observations, and quantitative tests. Interviews involved lecturers, students, and educational technology experts to explore implementation strategies and challenges of AI integration, while observations were conducted to observe the learning process. Quantitatively, the study used a quasi-experimental design by comparing the pre-test and post-test results between the experimental group (using AI) and the control group (conventional learning), each consisting of 32 students. Qualitative results show that AI-based learning management strategies are carried out systematically through needs mapping, selecting appropriate applications (such as GeoGebra AI and ChatGPT), and automatic monitoring of learning outcomes. AI encourages students to be more independent and interactive, although they still face technical constraints such as limited devices and internet networks. Quantitative results show a significant increase in the numeracy literacy skills of students in the experimental group compared to the control group, with the results of the independent sample t-test showing a significance value of 0.000 <0.05 and an average score difference of 10.11 points. These findings demonstrate that AI-based learning strategies are effective in strengthening students’ numeracy literacy and align with the principles of Sustainable Development Goal 4 (Quality Education). Therefore, AI integration in higher education is highly relevant for advancing sustainable educational practices and preparing future educators to meet the demands of Society 5.0.